Stable isotopic signatures in precipitation of 2006 southwest monsoon of Tamil Nadu - Chidambaram, S.; Prasanna, Mohan Viswanathan; Ramanathan, A.L.; Vasu, K.; Shahul Hameed, A.; Warrier, U.K.; Manivannan, R.; Srinivasamoorthy, K.; Ramesh, R. (Current Science, 2009)
Southwest monsoon (SWM) controls the majority ofthe agricultural activities in Tamil Nadu (TN), though the amount of rainfall received due to this is relatively less. The nature and behaviour of water vapour over TN reveal the other dynamic processes that are in operation during this period of the year. Hence, the stable isotope signatures of d 18O and dD obtained here were used to derive the first local meteoric water line for the State with SWM precipitation. The d-excess parameter was also used in conjunction and it was found that three dominant processes were in operation during this period: (i) vapours from southeast Arabian Sea, (ii) local evaporating vapours from inland tanks and (iii) vapours from the Indian Ocean.